Principles of diuretic therapy at liver cirrhosis - A. I. Dyadyk; T. Ye. Kugler; I. S. Malovichko; N. F. Yarovaya; I. V. Rakitskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present the key points of medical approach for treatment of edema syndrome (ascites, hydrothorax, dependent edema) at liver cirrhosis (LC). Key points. Most commonly LC is diagnosed at decompensated stage when portal hypertension becomes the leading syndrome. Generalized edema is the most common manifestation of portal hypertension which is associated with significant decrease in life quality, high risk of spontaneous bacterial complications, hepatorenal syndrome and poor prognosis. Diuretics play important role in the treatment of edema and prevention of relapses. The doctor should be aware of diuretic-related complications spectrum (hemodynamic, electrolytic, acid-base metabolism disorders) that will provide timely diagnostics and elimination and consequently, increase in treatment efficacy. Conclusion. Therapeutic approach for edema syndrome at LC should be based on series of fundamental steps: edema pathophysiology understanding; comprehensive investigation of patients; assessment of edema severity and presence of complications; awareness of pharmacological features of diuretic drugs, their interaction and side effects; albumin or plasma substitutes administration, use of vasoconstrictors, transjugular intrahepatic portosystemic shunting and liver transplantation when required.